Phytochemical compounds and antioxidant capacity of paederia foetida / Nor Habibah Mohd Rosli ... [et al.] - Mohd Rosli, Nor Habibah; Mohamad Shahrul, Nurdiyana Amira; Darimi, Siti Nur Liyana; Mohd Hassan, Melur Asmida; Samsudin, Afiqah Nasuha; Razihan, Siti Nurulhajar (Universiti Teknologi MARA Cawangan Pahang, 2021)
Paederia foetida is locally known as 'akar sekentut' or 'daun sekentut' because of the foul smell produced when the leaves are touched. It was used traditionally to reduce bloating and used by women after giving birth. This local species is overlooked because it is rarely found and often chopped off. Performing research on this species could help to enhance its medicinal value. Thus, this study attempts to analyse antioxidant capacity of fresh and dried leaves and twigs of P. foetida. The phytochemical constituents were initially screened, and the antioxidant capacity was evaluated by determining Total Phenolic Content (TPC), Total Flavonoid Content (TFC) and IC50 values using Follin-Ciocalteu method, AlCl3 method and DPPH assay, respectively. P. foetida showed the presence of phenolics, glycosides, alkaloids, saponins, tannins and terpenoids. The highest TPC and TFC were observed for methanolic extract of fresh twigs with 0.0536 GAE/g and methanolic extract of fresh leaves with 0.1545 QE/g respectively. The IC50 values ranged from 1.50 - 4.88 for all the ethanolic and methanolic extracts except for ethanolic extract of dried twigs of which the value was 16.88. The results obtained from this study revealed the potential of this local species as a promising natural antioxidant.